Oxygen-releasing biomaterials for osteoarthritis: advances in managing the hypoxic joint microenvironment - Wang, Ye; Chen, Zan; Huang, Wenjie; Liu, Mengkun; Zhao, Renliang; Deng, Xiangtian (Frontiers in Cell and Developmental Biology, 2025)
Osteoarthritis (OA) is a degenerative joint disease characterized by cartilage degeneration and osteophyte formation, with no fundamentally effective therapies currently available. Existing treatments are mainly symptomatic (e.g., drug injections and joint replacement) and cannot reverse the pathological progression, resulting in limited efficacy. A hypoxic microenvironment is a significant barrier to OA treatment: increased inflammatory cells in the synovium lead to higher oxygen consumption, causing cartilage hypoxia that exacerbates inflammation via hypoxia-inducible factors and accelerates cartilage damage. In recent years, research on oxygen-generating biomaterials targeting joint hypoxia has become a hot topic. Such materials continuously release oxygen through mechanisms like peroxide decomposition, enzyme-catalyzed reactions, or photosynthetic microbes, thereby increasing local oxygen partial pressure, relieving tissue hypoxia, and suppressing oxidative stress, which is expected to promote cartilage regeneration. This review systematically explores the hypoxia-induced pathogenic mechanisms of OA, innovatively categorizes and describes the fabrication strategies of oxygen-releasing biomaterials developed in recent years, analyzes their potential molecular mechanisms in OA therapy, and highlights current limitations in oxygen-release controllability and biosafety, as well as future research directions.